The Interest of Village Credit Institution Customers to Use the LPD Mobile Application with Trust as a Moderating Variable - Ni Luh Putu Ayu Lastri Pramiswari; Gayatri; I Wayan Suartana; I Ketut Sujana (International Journal of Social Science and Business, 2022)
The Village Credit Institution (LPD) aims to provide convenience for rural communities to obtain business capital and traditional costs. Although operating and serving customers in rural areas, LPD strives to keep up with technological developments by providing the LPD Mobile application. Seeing this phenomenon, this study aims to identify the use of determinants of LPD customer interest with trust as a moderating variable. This type of research is quantitative with a survey approach. Samples were taken from as many as 347 customers with the purposive sampling technique from a population of 99,108 customers. The method used in displaying the data is a questionnaire. The instrument used in collecting data is a questionnaire sheet. The analysis research results using Structural Equation Modeling based on Partial Least Square using SmartPLS 3.0 Software. The results show that ease of use and usability positively affect customer interest in using the LPD Mobile application. Trust cannot moderate the relationship between perceived ease of use and customer interest in using the LPD Mobile application. Trust can strengthen the positive relationship between usability and customer interest in using the LPD Mobile application.